Deslocamento de caracteres reprodutivos em Dendropsophus nanus (Anura, Hylidae) em sintopia e alopatria - Figueiredo, Estela Rodrigues [UNESP] (2014)
Character displacement can be important in the divergence of species, and for anurans, has been documented for acoustic parameters but seldom for other relevant aspects. Dendropsophus nanus and D. sanborni are closely related species similar in their morphology and ecology, and both can occur and reproduce in the same habitat. We tested the hypothesis that the advertisement calls and sites of vocalization of D. nanus have undergone character displacement in response to the presence of D. sanborni by comparing six call parameters and perch type and height between D. nanus found in three bodies of water in an area of allopatry and D. nanus found in three bodies of water in an area of syntopy with D. sanborni. We observed statistically significant differences in the type of perch used, but not perch height between the two areas. Among acoustic parameters, pulses produced by D. nanus were significantly shorter in syntopy than in allopatry, a result consistent with displacement of pulse duration in D. nanus in sintopia away from the longer pulse duration of D. sanborni. However, is possible that the differences observed in calls and vocalization site between syntopy and allopatry were also related to factors other than characters displacement, such differences between syntopy and allopatry in environmental, social and historical factors